Photovoltaic performance enhancement in CdTe thin-film heterojunction solar cell with Sb2S3 as hole transport layer. (December 2021) - Rahman, Sabrina; Ahmed, Sheikh Rashel Al
Highlights: CdTe-based solar cell with Sb2 S3 HTL has been modeled by SCAPS-1D. PV Performances of CdTe solar cells without and with HTL are investigated. Recombination loss at back side is reduced by adding Sb2 S3 HTL into CdTe solar cell. Enhanced efficiency of proposed CdTe solar cell with HTL is obtained to be 28.41%. Abstract: In this work, we design a novel cadmium telluride (CdTe)-based solar structure with antimony sulfide (Sb2 S3 ) as hole transport layer (HTL). One Dimensional Solar Cell Capacitance Simulator (SCAPS-1D) program is used to perform comparison studies on the photovoltaic performances between the standard thin-film cadmium sulfide (CdS)/CdTe solar cell and the proposed Al/FTO/CdS/CdTe/Sb2 S3 /Ni heterojunction structure. The solar cell outputs such as open-circuit voltage (Voc ), short-circuit current density (Jsc ), fill-factor (FF), and efficiency have been evaluated by varying impacts of thickness, electron affinity, carrier concentration, and bulk defect density of different layers. In addition, we have analyzed the effect of interface defects at both CdS/CdTe and CdTe/Sb2 S3 interfaces. This study reveals that the introduction of Sb2 S3 as HTL improves the Voc appreciably by creating appropriate band alignment with the CdTe absorber and thus remarkably enhance the efficiency of solar cell by lowering carrier recombination at back contact surface. Moreover, the impacts of working temperature, back contact metal work function, and surface recombination velocity are elucidated. The absorber thickness is optimized to be 1.0 µm with doping concentration of 2.1 × 10 15 cm −3 . Best efficiency of 28.41% together with other parameters such as Voc of 1.15 V, Jsc of 28.74 mA/cm 2, and FF of 86.03% is achieved for the optimized device. These results lead to suggest that the Sb2 S3 as HTL can be employed to fabricate highly efficient and inexpensive thin-film CdTe heterojunction solar devices.